A Methods engineering study on Gil Roy's Garlic Enterprises - Alombro, Kevin; Mercado, Donnabelle Kristia V.; Santos, Allan T. (Diliman, Quezon City College of Engineering, 2000)
The subject of this Methods Engineering study is Gil Roy's Garlic Enterprises situated at #40 Rodriguez St., Bayan-bayanan, Malabon. The business type is single proprietorship and the nature of business is mass production. The company produces fried garlic granules, chips and flakes and its customers include restaurants, such as Kenny Roger's Malabon and supermarkets. The raw materials used are raw garlic, cooking oil, and a special food additive. The production section covers an area of 120 square meters. The company employs a total of thirteen (13) people : 1 overall supervisor, 1 cooking supervisor, 1 cooking supervisor, 1 sales representative, 3 slicers/driers, 3 washers/sifters, 2 cooks and 2 packagers. The function of the proprietor includes planning, purchasing, accounting, and marketing. Different procedures apply to different customers with regards to placement of orders. For supermarkets, order placement is accomplished after an Overall Count of Stocks (OCS) has been made from which they determine whether the stock needs replenishment. For restaurants, a purchase order form is faxed to the company. Production processes include washing of peeled garlic, slicing, sifting, re-slicing, chemical treatment, frying, drying, quality control, temporary storage, and packaging. The company uses 3 food processors in slicing the peeled garlic. In sifting, a wire mesh is used of size 1/4 x 1/4 inch in separating acceptable slices of garlic from those needing reslice. Sliced garlic is soaked in water with special food additive in it for an hour in order to extricate starch so that fried garlic will maintain crispness. Sliced garlic is fried in three cooking pans with regular gas stove as heat source. After drying, quality control is achieved through visual inspection, picking out half-cooked garlic. The product is packaged in 3 x 5 inches plastic sachets and in 8 ounce bottles.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis